Eccentric external and internal rotation peak torque ratios predict shoulder injuries with national judokas; a prospective cohort study - Darbandi, S. M.; Sebyani, M.; Behpour, S.; Behm, D. G.; Hosseinzadeh, M. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Introduction and aim This study aimed to identify isokinetic strength variables of the shoulder rotator muscles that are associated with the risk of upper limb injuries in elite judokas, and to establish predictive cut-off values for injury risk using a prospective cohort design.